![](https://rs.olm.vn/images/avt/0.png?1311)
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
\(2x-8x^2=0\Rightarrow2x\left(1-4x\right)=0\Rightarrow\orbr{\begin{cases}2x=0\\1-4x=0\end{cases}\Rightarrow\orbr{\begin{cases}x=0\\x=\frac{1}{4}\end{cases}}}\)
\(x-x^2=0\Rightarrow x\left(1-x\right)=0\Rightarrow\orbr{\begin{cases}x=0\\1-x=0\end{cases}\Rightarrow\orbr{\begin{cases}x=0\\x=1\end{cases}}}\)
Cn lại lm tương tự nha e!
=.= hok tốt!!
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
1) \(3\left(5x-2\right)-9=6\)
\(15x-6=6+9\)
\(15x=15+6\)
\(15x=21\)
\(x=\frac{7}{5}\)
2) \(4\left(3x-2\right)+7\left(3x-2\right)=22\)
\(\left(3x-2\right)\left(4+7\right)=22\)
\(\left(3x-2\right)\cdot11=22\)
\(\left(3x-2\right)=2\)
\(3x=4\)
\(x=\frac{4}{3}\)
3) \(2x^2-6x=0\)
\(2x\left(x-3\right)=0\)
\(\Rightarrow\orbr{\begin{cases}2x=0\\x-3=0\end{cases}}\)
\(\Rightarrow\orbr{\begin{cases}x=0\\x=3\end{cases}}\)
Vậy,............
\(1)3\left(5x-1\right)-9=6\)
\(\Rightarrow3\left(5x-2\right)=15\)
\(\Rightarrow5x-2=5\Rightarrow5x=7\Rightarrow x=\frac{7}{5}\)
\(2)4\left(3x-2\right)+7\left(3x-2\right)=22\)
\(\Rightarrow11\left(3x-2\right)=22\)
\(\Rightarrow33x-22=22\Rightarrow33x=44\Rightarrow x=\frac{4}{3}\)
\(3)2x^2-6x=0\)
\(\Rightarrow2x\left(x-2\right)=0\)
\(\Rightarrow\orbr{\begin{cases}2x=0\\x-2=0\end{cases}}\Rightarrow\orbr{\begin{cases}x=0\\x=2\end{cases}}\)
![](https://rs.olm.vn/images/avt/0.png?1311)
\(a,x=3x^2\Rightarrow x-3x^2=0\Rightarrow x\left(1-3x\right)=0\Rightarrow\orbr{\begin{cases}x=0\\1-3x=0\end{cases}}\Rightarrow\orbr{\begin{cases}x=0\\x=\frac{1}{3}\end{cases}}\)
\(b,\left(2x-6\right)\left(x+4\right)+2\left(2x-6\right)=0\)
\(\Rightarrow\left(2x-6\right)\left(x+4+2\right)=0\)
\(\Rightarrow\left(2x-6\right)\left(x+6\right)=0\)
\(\Rightarrow\orbr{\begin{cases}2x-6=0\\x+6=0\end{cases}}\Rightarrow\orbr{\begin{cases}x=3\\x=-6\end{cases}}\)
\(c,\left(2x-5\right)\left(x+9\right)+6x-15=0\)
\(\Rightarrow\left(2x-5\right)\left(x+9\right)+3\left(2x-5\right)=0\)
\(\Rightarrow\left(2x-5\right)\left(x+9+3\right)=0\)
\(\Rightarrow\left(2x-5\right)\left(x+12\right)=0\)
\(\Rightarrow\orbr{\begin{cases}2x-5=0\\x+12=0\end{cases}}\Rightarrow\orbr{\begin{cases}x=\frac{5}{2}\\x=-12\end{cases}}\)
![](https://rs.olm.vn/images/avt/0.png?1311)
Bài 1 : a) 3x2 +21x=0
3x(x+7)=0
=> x=0 hoặc x+7=0 =>x=0 hoặc x= -7
b)5x-6x2=0
x(5-6x)=0
=> x=0 hoặc 5-6x=0 => x=0 hoặc x=\(\frac{5}{6}\)
\(3x^2+21x=0\)
\(\Rightarrow3x\left(x+7\right)=0\)
\(\Leftrightarrow\orbr{\begin{cases}3x=0\\x+7=0\end{cases}}\Leftrightarrow\orbr{\begin{cases}x=0\\x=-7\end{cases}}\)
\(5x-6x^2=0\)
\(\Rightarrow x\left(5-6x\right)=0\)
\(\Leftrightarrow\orbr{\begin{cases}x=0\\5-6x=0\end{cases}\Leftrightarrow\orbr{\begin{cases}x=0\\x=\frac{5}{6}\end{cases}}}\)
\(\left(2x+3\right)\left(y-5\right)=0\)
\(\Leftrightarrow\orbr{\begin{cases}2x+3=0\\y-5=0\end{cases}\Leftrightarrow\orbr{\begin{cases}x=-\frac{3}{2}\\x=5\end{cases}}}\)
2x2 - 6x = 0
\(\Rightarrow\)x(2x - 6) = 0
\(\Rightarrow\orbr{\begin{cases}x=0\\2x-6=0\end{cases}}\)
\(\Rightarrow\orbr{\begin{cases}x=0\\x=3\end{cases}}\)
2x2 - 6x = 0
2x.(x-3) = 0
=> x = 0
x-3 = 0=> x = 3
KL:>..